2015
DOI: 10.1111/imm.12417
|View full text |Cite
|
Sign up to set email alerts
|

The presence of interleukin‐27 during monocyte‐derived dendritic cell differentiation promotes improved antigen processing and stimulation of T cells

Abstract: SummaryDendritic cells (DCs) are potent antigen-presenting cells necessary to establish effective adaptive immune responses. The cytokine environment that exists at the time of DC differentiation may be an important but often ignored determinant in the phenotypic and functional properties of DCs. Interleukin-27 (IL-27) is a unique cytokine that has both inflammatory and immune suppressive activities. Although it can both promote and oppose activity of different T-cell subsets, mostly anti-inflammatory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
(134 reference statements)
1
24
0
Order By: Relevance
“…IL-27 stimulation can significantly improve Treg function both in vitro and in vivo. Type I IFN can also induce Treg phenotype polarization [15,16,17,18]. In this study, we observed the increases of IL-27 and IFN expression in untreated GFP-Aire/DC.…”
Section: Discussionsupporting
confidence: 54%
“…IL-27 stimulation can significantly improve Treg function both in vitro and in vivo. Type I IFN can also induce Treg phenotype polarization [15,16,17,18]. In this study, we observed the increases of IL-27 and IFN expression in untreated GFP-Aire/DC.…”
Section: Discussionsupporting
confidence: 54%
“…By contrast, short-term stimulation of MΦs with IL-4 delayed the acquisition of phagosome maturation markers and phagosomal acidification after uptake of immunoglobulin G (IgG)-opsonized zymosan [44]. Moreover, stimulation of DCs with IL-27 for several days induced enhanced phagosomal acidification, as measured by increased co-localization of phagosomes with lysotracker, and enhanced acquisition of proteolytic enzymes, such as cathepsin D [45]. By contrast, stimulation of DCs with TNF and CD40 ligand did not induce major differences in phagosomal degradation [36].…”
Section: Impact Of Immune Signals On Phagosome Maturationmentioning
confidence: 99%
“…5,6 IL-27 was first identified for its role in differentiation of na€ ıve T cells to a Th1 phenotype and the ability to augment IL-12-induced IFN-c production. 6,7 Although inflammatory activity toward human monocytes and dendritic cells, as well as antiretroviral activity have been reported, [8][9][10][11][12][13] a multitude of reports point to immune suppressive influences that may dominate IL-27 biology. Collectively, IL-27 has been shown to limit Th1, Th2 and Th17 responses while inducing T regulatory cells.…”
Section: Introductionmentioning
confidence: 99%